Ultrastructural analysis and residual DNA evaluation of rabbit vein scaffold - Bertanha,Matheus (2017)
Abstract Purpose: To investigate the ultrastructural characteristics and analysis of residual DNA in scaffold models, produced with decellularized vena cava in an experimental model with rabbits. Methods: Three groups were created for ultrastructural and residual DNA analysis: group 1 - control, consisting of samples of vena cava in natura; group 2 - SD, consisting of vein fragments submitted to 2% sodium deoxycholate decellularization by shaking (160rpm - Shaker News Brunswick Scientific®) for 1 hour at controlled temperature shaker at 37°C; group 3 - SDS, consisting of vein fragments submitted to 1% sodium dodecyl sulfate decellularization under the same previous condition, for 2 hours. Results: The ultrastructural matrix of the blood vessel maintained its vintegrity after either decellularization models. The results of the two quantification methods demonstrated a significant decrease in the DNA content of the decellularized vena cava samples as compared to the control samples and, differed statistically from each other, p <0.05. Conclusion: The 2% DS protocol for vein decellularization, in this experimental model, was considered the best protocol because it presented less amount of residual DNA without causing substantial destruction of the extracellular matrix.